Methylglyoxal, the dark side of glycolysis - Allaman, Igor; Bélanger, Mireille; Magistretti, Pierre J. (Frontiers in Neuroscience, 2015)
Glucose is the main energy substrate for the brain. There is now extensive evidence indicating that the metabolic profile of neural cells with regard to glucose utilization and glycolysis rate is not homogenous, with a marked propensity for glycolytic glucose processing in astrocytes compared to neurons. Methylglyoxal, a highly reactive dicarbonyl compound, is inevitably formed as a by-product of glycolysis. Methylglyoxal is a major cell-permeant precursor of advanced glycation end-products (AGEs), which are associated with several pathologies including diabetes, aging and neurodegenerative diseases. The glyoxalase system is the most important pathway for the detoxification of methylglyoxal, and although the neurotoxic effects of methylglyoxal and AGEs are well characterized, less is known about the glyoxalase system in the brain. Considering the high energy requirements (i.e. glucose) of the brain, one should expect that the cerebral glyoxalase system is adequately fitted to handle methylglyoxal toxicity. This review focuses on our actual knowledge on the cellular aspects of the glyoxalase system in brain cells, in particular with regards to its activity in astrocytes and neurons. A main emerging concept is that a neuroenergetic specialization is taking place between these two cell types which may serve as a protective mechanism against methylglyoxal-induced toxicity.